The neglect of protection for undocumented Migrant Workers within the framework of Human Rights Law - Rahayu, Devi; Supaat, Dina Imam; Yusuf, Mirna (Legality : Jurnal Ilmiah Hukum, 2024)
The safeguarding of fundamental rights for undocumented migrant workers represents a critical challenge that necessitates immediate attention. This article addresses the oversight within the human rights discourse regarding the fundamental rights of undocumented migrant workers. Through empirical normative research, incorporating a comprehensive review of normative literature, this study critically examines the regulations affecting migrant workers through the lens of human rights. It identifies a significant correlation between the lack of protective guarantees for undocumented migrant workers and the various cases and consequences that ensue. From a human rights perspective, regulations prioritize equality before the law, protection, and anti-discrimination. This stance contrasts with existing laws that govern Indonesian migrant workers, wherein protection is exclusively extended to those legally recognized. Such exclusivity denies undocumented migrant workers the assurance of their fundamental rights. Arguably, the provision of basic rights and protections should be indiscriminately extended to all migrant workers, irrespective of their legal status. While the specifics of migrant worker placement can still be regulated concerning requirements, processes, involved parties, and responsibilities, these regulations must not infringe upon the fundamental human rights of individuals. Consequently, this paper advocates for a thorough evaluation of current legislation with respect to its content, the comprehension of involved stakeholders, and the practical implementation of regulations concerning the management of migrant workers.